2021
DOI: 10.3390/ani11102768
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mRNA and Long Non-Coding RNA Expression Profiles in Developing Yorkshire Pig Spleens

Abstract: Epidemic diseases cause great economic loss in pig farms each year; some of these diseases are characterized mainly in the spleen, but mRNA and lncRNA (long non-coding RNA) expression networks in developing Yorkshire pig spleens remain obscure. Here, we profiled the systematic characters of mRNA and lncRNA repertoires in three groups of spleens from nine Yorkshire pigs, each three aged at seven days, 90 days, and 180 days. By using a precise mRNA and lncRNA identification pipeline, we identified 19,647 genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Compared to 14 vs. 1 d and 28 vs. 1 d, the number of differential mRNAs and lncRNAs in 28 vs. 14 d is significantly lower. We speculate that the immune system of piglets starts to establish itself before 14 days, which is in general agreement with the view that the immune system of pigs is established at seven days of life (43).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to 14 vs. 1 d and 28 vs. 1 d, the number of differential mRNAs and lncRNAs in 28 vs. 14 d is significantly lower. We speculate that the immune system of piglets starts to establish itself before 14 days, which is in general agreement with the view that the immune system of pigs is established at seven days of life (43).…”
Section: Discussionsupporting
confidence: 91%
“…The spleen is one of the pigs' most important immune organs. Additionally, studies have reported many epidemics in pigs to be associated with spleen damage, such as PRRS, Porcine Circovirus, pseudorabies, and swine fever ( 43 ). There are two existing studies on lncRNAs in the spleen of Chinese endemic pigs, and these studies focused on the multiple developmental stages of the pig spleen ( 22 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, FERH regulates signal transduction, intracellular signaling cascade, and glucose and lipid metabolism. rrp7a proteins regulate immune response, the proliferation of blood cells [ 34 ]. ATP10A is a transmembrane protein in the p-type cation transport ATPase family [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has established that LncRNA-Cox2 regulates macrophage polarization and inflammatory responses in septic mice via the CREB-C/EBP signaling pathway [ 10 ]. In addition, Qiao et al [ 11 ] have provided transcriptome profiles of mRNAs and lncRNAs at development stages in Yorkshire pigs. However, no studies have explored lncRNA-mRNA interactions during the spleen developmental stages of Meishan pigs.…”
Section: Introductionmentioning
confidence: 99%